2019
DOI: 10.1186/s42836-019-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgical approach on early complications of total hip arthroplasty

Abstract: Background: Total hip arthroplasty (THA) is traditionally associated with a low complication rate, with complications such as infection, fracture and dislocation requiring readmission or reoperation. We seek to identify the complication rate among the anterior, direct lateral and posterior surgical approaches. Methods: We reviewed all THAs performed at the Epworth Healthcare from 1 July 2014 to 30 June 2016. There were 2437 THAs performed by a variety of approaches. No hips were excluded from this study. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Woolson et al [15] reported that among inexperienced surgeons it was the main complication with 6.5% of femoral shaft or GT fracture. Tay et al [28] undertook a comparison between anterior, lateral, and posterior approach: anterior approach appeared to be the approach with the higher rate of complications (3.1%), mostly due to PFF (1.4%). The low rate of PFF in this study (1%) could be explained by the non-use of an extension table which is known to put more constraint on the femur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woolson et al [15] reported that among inexperienced surgeons it was the main complication with 6.5% of femoral shaft or GT fracture. Tay et al [28] undertook a comparison between anterior, lateral, and posterior approach: anterior approach appeared to be the approach with the higher rate of complications (3.1%), mostly due to PFF (1.4%). The low rate of PFF in this study (1%) could be explained by the non-use of an extension table which is known to put more constraint on the femur.…”
Section: Discussionmentioning
confidence: 99%
“…Five hundred and twenty five THA performed on 474 patients were included retrospectively from May 2013 to December 2017 in a university training hospital. Three hundred and sixty one THA were performed by a senior surgeon and 164 by six junior surgeons (mean = 27 patients [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ± 8) with the same experience (five years of residency learning PA) supervised by the senior. The senior surgeon had performed the DAA technique for one year before supervising the trainees.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, data from a large Australian private hospital comparing 949 anterior THA, 870 posterior and 618 lateral THA, found the anterior approach to have more periprosthetic fractures treated with internal fixation at the time of the index procedure, and also a higher rate of revisions for periprosthetic fracture in the first 30 days. 34 Complications have been shown to relate to surgeon experience and learning curve, 35 and potentially implant choice. 36 The results of our study may have been positive for the anterior approach given that many of the surgeons performing anterior THA had completed their learning curve and we have adjusted for year of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although anterior approach THA can be technically demanding, with difficult exposure and femoral access, requiring longer surgical time, 27,32,33 and greater blood loss, 33 our study showed that this may not result in an overall higher complication rate in the short term. In contrast, data from a large Australian private hospital comparing 949 anterior THA, 870 posterior and 618 lateral THA, found the anterior approach to have more periprosthetic fractures treated with internal fixation at the time of the index procedure, and also a higher rate of revisions for periprosthetic fracture in the first 30 days 34 . Complications have been shown to relate to surgeon experience and learning curve, 35 and potentially implant choice 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Different treatment concept assumes a postoperative early mobilization program. Larger value of BMI is associated with longer LOS and increasing costs [24].…”
Section: Discussionmentioning
confidence: 99%